Split the inequality into two:
(-4x+14)>6 & -(-4x+14)>6
solve:
(-4x+14)>6
-4x>-8
x<2
(symbol changes when ÷/× by negative for inequalities.)
-(-4x+14)>6
-4x+14<-6
-4x<-20
x>5
the answers are x<2 and x>5, so you would write your answer like this: (-∞,2) ∪ (5,∞)
Answer:
x = 13
Step-by-step explanation:
This question is based on Secant Secant theorem.
Secant Secant theorem gives us the following formula:
(AB + BD)AB = (AC + CE).AC
From the above question we have the following parameters
AB = 5
BD = x
AC = 7.5
CE = 4.5
Hence,
(AB + BD)AB = (AC + CE).AC
(5 + x)5 = (7.5 + 4.5)7.5
25 + 5x = 90
Collect like terms
5x = 90 - 25
5x = 65
x = 65/5
x = 13
Answer:
I dont now cause it depends on what you teacher asks of you
Answer:
256, 1024, 4096.
Step-by-step explanation:
The rule is x*4.
--> 1*4 = 4.
--> 4*4 = 16.
--> 16*4 = 64.
--> 64*4 = 256.
--> 256*4 = 1024.
--> 1024*4 = 4096.